The Use of Interactive Worksheet to Teach Speaking - Ansah, Andre; Athena, Tera; Mastuti, Endang (Acitya: Journal of Teaching and Education, 2024)
The purpose of the study is to show how Interactive Worksheets can be used to deliver speaking. The interactive worksheet was made by the instructor and is accessible online to encourage students to speak more. Students get the chance to express themselves in a stress-free and enjoyable way. The study used a descriptive qualitative research design and methodology. The sources of the data are the online interactive worksheet and the responses from students to it. Data collection techniques include observation, interviewing, and documentation. The triangulation methodology is used by the researcher to evaluate the data's adequacy Techniques for analyzing data include data condensing, data displaying, conclusion, and verification. The study's findings indicate that: First, help students practice speaking aloud without pressure. Secondly, encouraging their creative learning and speaking. Third, concentrate on assisting the students in developing their speaking skills. Just have fun when they speak, that's all. The disadvantage is that students may find it challenging to understand and accurately pronounce terms used in the text. In order to look up challenging terms, students can implement lively game combinations. The researcher offers suggestions for future research, educators, and students in this study.